CHARACTERIZATION OF TRANSITIONAL EPITHELIUM IN THE NORMAL RAT BLADDER USING THE MORPHOMETRIC AND CLUSTER ANALYSIS - Токарук, Н.С. (World of Medicine and Biology, 2014)
For cluster analysis we used agglomerative hierarchical method and iterative method of k-means. In cellular composition of transitional epithelium four clusters and their morphometric parameters were determined. Cluster 1 takes the smallest share (10.96%), and cell clusters 2, 3 and 4 are respectively 39.47%, 34.21% and 15.35%. Cluster 1 contains the smallest undifferentiated basal cells with high nuclear cytoplasmic ratio (NCR). They act as cambial committed cells that proliferate and regenerate cellular composition of the urothelium. Cluster 4 contains major superficial urothelial cells with the lowest NCR. They are highly differentiated umbrella cells that actually form an urothelial barrier. Clusters 2 and 3 are formed by intermediate layer cells of the transitional epithelium. Cells from cluster 2 are moderately differentiated. They characterize the initial stage of urothelial cells differentiation. Cells from cluster 3 are highly differentiated. They characterize terminal differentiation. It was also determined that the cellular structure of clusters 1 and 4, 2 and 3 are in a particular functional equilibrium. The resulting cluster structure characterizes the urothelial cells population in transitional epithelium of the normal (annual, male) rat bladder.